The merlin conspiracy - Jones, Diana Wynne (Great Britain : HarperCollins Publishers Ltd, 2003)
Roddy and Nick, two teenagers with magical powers they are just learning to use, find that they must work together to save Roddy's home world of Blest from destruction by power-hungry wizards
Keywords: Magic -- Juvenile fiction; Self-perception -- Juvenile fiction; English fiction